Models of cardiovascular surgery biobanking to facilitate translational research and precision medicine. (21st December 2021) - Zhu, YingYan; Jackson, Dan; Hunter, Benjamin; Beattie, Lorna; Turner, Lisa; Hambly, Brett D.; Jeremy, Richmond W.; Malecki, Cassandra; Robertson, Elizabeth N.; Li, Amy; dos Remedios, Cris; Richmond, David; et al.
Abstract: Biobanking in health care has evolved over the last few decades from simple biological sample repositories to complex and dynamic units with multi‐organizational infrastructure networks and has become an essential tool for modern medical research. Cardiovascular tissue biobanking provides a unique opportunity to utilize cardiac and vascular samples for translational research into heart failure and other related pathologies. Current techniques for diagnosis, classification, and treatment monitoring of cardiac disease relies primarily on interpretation of clinical signs, imaging, and blood biomarkers. Further research at the disease source (i.e. myocardium and blood vessels) has been limited by a relative lack of access to quality human cardiac tissue and the inherent shortcomings of most animal models of heart disease. In this review, we describe a model for cardiovascular tissue biobanking and databasing, and its potential to facilitate basic and translational research. We share techniques to procure endocardial samples from patients with hypertrophic cardiomyopathy, heart failure with reduced ejection fraction, and heart failure with preserved ejection fraction, in addition to aortic disease samples. We discuss some of the issues with respect to data collection, privacy, biobank consent, and the governance of tissue biobanking. The development of tissue biobanks as described here has significant scope to improve and facilitate translational research in multi‐omic fields such as genomics, transcriptomics, proteomics, and metabolomics. This research heralds an era of precision medicine, in which patients with cardiovascular pathology can be provided with optimized and personalized medical care for the treatment of their individual phenotype.